The paradox of the narrative event in John Barth's "Lost in the Funhouse" - Abu Jweid, Abdalhadi Nimer Abdalqader; Ali Termizi, Arbaayah (Universiti Putra Malaysia Press, 2015)
This article explores, via a postmodern approach, how Barth dealt with the intricate relationship between postmodern fiction and its modern counterpart by constructing a subjective narrative event in his novella, "Lost in the Funhouse". It examines the transparent and correspondent representation of the narrative event as a category of Barthian critique of modern literary exhaustion, and how Barth appropriates remedial recycling for fictional conventions. This apocalyptic homogeneous narrative device involves a constant reciprocal examination of contemporary fiction and its possible future. It is carried out through mutual subversion and, ultimately, challenges the notion of inherited literary forms and their utilisation over time. As such, the whole narrative event is achieved via a self-reflexive trajectory and multifarious textual solipsism.